2016
DOI: 10.15244/pjoes/61715
|View full text |Cite
|
Sign up to set email alerts
|

Finding Probability Distributions for Annual Daily Maximum Rainfall in Pakistan Using Linear Moments and Variants

Abstract: In this study, at-site frequency analysis (AFA) of an annual daily maximum rainfall (ADMR) series was carried out using the method of linear moments (L-moments) and their variants such as trimmed linear moments (TL-moments) and higher order linear moments (LH-moments). The ADMR series we investigated was observed at 28 meteorological observatories across Pakistan as retrieved from the Pakistan Meteorological Department (PMD). The basic aim of the study was to fi nd best-fi t (i.e., the most suitable) probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The guidelines were first published in 1958and updated thereafter in 1977and 1978(Pilgrim, 1984, and have been continually updated. Compared to the previous revision, the most recent update makes use of nearly 30 years of additional daily rainfall data from 2 300 additional rainfall stations and was published in 2016 (Ball et al, 2016). Design rainfalls are categorised into five broad classes, based on the frequency of occurrence, as summarised in Table 1.…”
Section: Design Rainfalls In Australiamentioning
confidence: 99%
See 1 more Smart Citation
“…The guidelines were first published in 1958and updated thereafter in 1977and 1978(Pilgrim, 1984, and have been continually updated. Compared to the previous revision, the most recent update makes use of nearly 30 years of additional daily rainfall data from 2 300 additional rainfall stations and was published in 2016 (Ball et al, 2016). Design rainfalls are categorised into five broad classes, based on the frequency of occurrence, as summarised in Table 1.…”
Section: Design Rainfalls In Australiamentioning
confidence: 99%
“…This is considered to be a good compromise between providing a better fit to the higher probabilities of the distribution and giving too much influence to the high outliers . Many countries are exploring the use of LH-moments for estimating extreme rainfall and flood events (Ahmad et al, 2016;Deka et al, 2011;Hossein and Gheidari, 2013).…”
Section: Design Rainfalls In Australiamentioning
confidence: 99%
“…According to the United Nations Framework on Climate Change (UNFCC) the human lives, animal lives, and water resources, agricultural lands, food security, and coastal zones will be heavily affected Value (GEV), Gumbel, Generalized Pareto (GP), Generalized Logistic (GLO) and the lognormal distribution. Because of their suitability to modelling of extreme value, these probability distributions have numerous applications for environmental data (e.g., An and Pandey, 2005;Furrer and Katz, 2008;Chikobvu and Sigauke, 2013;Jonathan and Ewans, 2013;Diriba et al, 2015;Ahmad et al, 2016). Several studies based on frequentist approaches have been conducted for finding the best fit distribution and modelling the AMDR data in Pakistan by Rasul et al (2004), Haroon and Rasul (2009), Rasul et al (2009) and Ahmad et al (2014Ahmad et al ( , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their suitability to modelling of extreme value, these probability distributions have numerous applications for environmental data (e.g., An and Pandey, 2005;Furrer and Katz, 2008;Chikobvu and Sigauke, 2013;Jonathan and Ewans, 2013;Diriba et al, 2015;Ahmad et al, 2016). Several studies based on frequentist approaches have been conducted for finding the best fit distribution and modelling the AMDR data in Pakistan by Rasul et al (2004), Haroon and Rasul (2009), Rasul et al (2009) and Ahmad et al (2014Ahmad et al ( , 2016. Ahmad et al (2016) suggested that the (GEV) and (GP) are the most suitable distribution for the AMDR series in the different regions of Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain -Abbas: Rainfall frequency analysis using Frechet and Log-logistic distributions of sites of Azad Jammu and Kashmir, Hungary rainfall of 30 met sites of Pakistan. The study area (includes sites from Sindh, Punjab, Balochistan and Northern Areas) was divided into four homogeneous regions with different three-parameters probability distributions identified as best-fitted probability distributions Ahmad et al (2016). performed at site frequency analysis using annual daily maximum rainfall series.…”
mentioning
confidence: 99%